'De Haene' house, Meelstraat 1 in Zierikzee (Bulletin KNOB, 2005)
In the fifteenth century the house 'de Haene' was built in the commercial town of Zierikzee, later incorrectly known as the 'Tempelierenhuis' (house of the Knights Templar). Not many written sources have been preserved. The house remained in private hands for a long time: in the second half of the 18th century it was owned by a plumber, later by a coppersmith.The present, still existing division of the house into two parts dates a long way back. Serious decay led to gradual repairs, accompanied with a lot of problems. First as the local authority, later as the owner, the municipality of Zierikzee, now Schouwen-Duiveland, played an active role to realise these repairs. The last phase was the recently completed restoration of the façade.Archaeological research has produced limited information. Internal research in the house was not possible, but would also have produced limited results, because of the drastic renovations carried out in the past. On the other hand, the façade was not dramatically altered through the centuries.Consequently, it is among the most extraordinary late-medieval façades in the Netherlands. Remarkable is the composition of the use of materials: natural stone up to the attic floor, above this practically only brick. Preservation was an important aim in the restoration, including the preservation of the patina. Only the substructure, notably the entrances to the cellar and main floor, was more or less restored to resemble the original situation.